Virilizing Adrenocortical Carcinoma Oncocytic Variant in a Child with Heterosexual Precocious Puberty and a Literature Review - Seyran Bulut; Gönül Çatlı; Berna Eroğlu Filibeli; Hayrullah Manyas; İlkay Ayrancı; Rabia Meral; Deniz Kızmazoğlu; Bumin Nuri Dündar (Galenos Yayinevi, 2022)
Androgen-secreting adrenal tumors are aggressive cancers in childhood; however, they are rare in clinical practice. Children with adrenal carcinoma usually present with peripheral precocious puberty, premature pubarche, signs of virilization and clitoromegaly. We present a case of 4 year-old girl with premature pubarche, clitoromegaly and bone age advancement, who was subsequently diagnosed with pure androgen-secreting oncocytic adrenal carcinoma. After the removal of the adrenal tumor, our patient developed precocious puberty. In patients with functioning adrenocortical carcinoma who have had surgical removal, clinical follow-up and hormonal marker examination for the secondary effects of excessive hormone secretion at least every 2 or 3 months may be a useful option after surgery. The aim of this article is to emphasize that adrenal tumors can be seen in patients presenting with virilization findings. We also present a literature review of these tumors, which are very rare in childhood.